Prognostic benefit of urgent cardiac surgery in left-sided infective endocarditis. (25th November 2020) - Garcia Granja, P.E; Lopez, J.A; Ladron, R; Cabezon, G; Vilacosta, I; Dominguez, F; Olmos, C; Sarria, C; Lopez, I; Carrasco, M; Garcia-Pavia, P; San Roman, A
Abstract: Background: Cardiac surgery is required in approximately 50% of patients with left-sided infective endocarditis (IE) being a high-risk procedure specially during active phase of the disease. Purpose: To evaluate the impact of cardiac surgery in the in-hospital mortality of left-sided IE. Methods: We used a prospective cohort of consecutive patients with definite left-sided IE between 2000 and 2017 (n=1002). A predictive model of in-hospital mortality was derived by adding the variable cardiac surgery to the already published ENDOVAL score. The benefit of cardiac surgery was calculated with the mean difference between the risk of in-hospital mortality considering urgent surgery and considering no surgery for each patient. Results: The predictive model showed good discriminative capacity with an area under the ROC curve of 0.861 (95% CI: 0.830 - 0.891) and a good calibration (p-value in the Hosmer-Lemeshow test of 0.353). Figure shows the in-hospital mortality prediction of each patient in case of no-surgery (orange), urgent surgery (yellow) or real decision (blue). Mean reduction of in-hospital mortality risk in case of surgery for patients with a theoretical risk of in-hospital mortality between 0–20% in absence of surgery was 3.2±1.6%. For patients with a theoretical risk between 20–40% in absence of surgery the mean reduction was 8.1±1.1%. For patients with a theoretical risk between 40–60% in absence of surgery the mean reduction was 10.7±0.3%. For patients with a theoretical risk between 60–80% in absence of surgery the mean reduction was 9.7±0.9%. For patients with a theoretical risk between 80–100% in absence of surgery the mean reduction was 4.6±2.1%. Conclusion: Urgent cardiac surgery is a protective factor of in-hospital mortality for all patients with left-sided IE but especially for those with intermediate risk. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Gerencia Regional de Salud, Junta de Castilla y Leόn